Characterization and comprehensive genome analysis of novel bacteriophage, vB_Kpn_ZCKp20p, with lytic and anti-biofilm potential against clinical multidrug-resistant Klebsiella pneumoniae - Zaki, Bishoy Maher; Fahmy, Nada A.; Aziz, Ramy Karam; Samir, Reham; El-Shibiny, Ayman (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The rise of infections by antibiotic-resistant bacterial pathogens is alarming. Among these, Klebsiella pneumoniae is a leading cause of death by hospital-acquired infections, and its multidrug-resistant strains are flagged as a global threat to human health, which necessitates finding novel antibiotics or alternative therapies. One promising therapeutic alternative is the use of virulent bacteriophages, which specifically target bacteria and coevolve with them to overcome potential resistance. Here, we aimed to discover specific bacteriophages with therapeutic potential against multiresistant K. pneumoniae clinical isolates. Methods and Results Out of six bacteriophages that we isolated from urban and medical sewage, phage vB_Kpn_ZCKp20p had the broadest host range and was thus characterized in detail. Transmission electron microscopy suggests vB_Kpn_ZCKp20p to be a tailed phage of the siphoviral morphotype. In vitro evaluation indicated a high lytic efficiency (30 min latent period and burst size of ∼100 PFU/cell), and extended stability at temperatures up to 70°C and a wide range of (2-12) pH. Additionally, phage vB_Kpn_ZCKp20p possesses antibiofilm activity that was evaluated by the crystal violet assay and was not cytotoxic to human skin fibroblasts. The whole genome was sequenced and annotated, uncovering one tRNA gene and 33 genes encoding proteins with assigned functions out of 85 predicted genes. Furthermore, comparative genomics and phylogenetic analysis suggest that vB_Kpn_ZCKp20p most likely represents a new species, but belongs to the same genus as Klebsiella phages ZCKP8 and 6691. Comprehensive genomic and bioinformatics analyses substantiate the safety of the phage and its strictly lytic lifestyle. Conclusion Phage vB_Kpn_ZCKp20p is a novel phage with potential to be used against biofilm-forming K. pneumoniae and could be a promising source for antibacterial and antibiofilm products, which will be individually studied experimentally in future studies.